2018
DOI: 10.1007/s00181-018-1481-0
|View full text |Cite
|
Sign up to set email alerts
|

“Sakura” has not grown in a day: infrastructure investment and economic growth in Japan under different tax regimes

Abstract: This paper explores whether the validity of infrastructure investment serves as a procyclical or anticyclical instrument to counter a recession in the case of the Japanese economy. Infrastructure consumption is usually financed by taxes. For that reason, this paper accounts for the presence of alternative tax regimes. Namely, we have chosen regimes under Total Taxation, Capital Taxation, Corporate (Income) Taxation, Household Income Taxation and Indirect Taxation (valued added tax) to identify different policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…It is related to the development trend of the national economy and the quality of people's survival, and it is regarded as one of the most important elements of national development competitiveness. In general, by strengthening investment in infrastructure and technological innovation in infrastructure, the upgrading of the industrial structure has been promoted, and a new growth point has been provided for the development of the national economy [ 9 ]. Other researchers believe that the establishment and use of infrastructure in a developing country have a very critical significance in promoting the long-term sustainable development of its economy and society.…”
Section: Introductionmentioning
confidence: 99%
“…It is related to the development trend of the national economy and the quality of people's survival, and it is regarded as one of the most important elements of national development competitiveness. In general, by strengthening investment in infrastructure and technological innovation in infrastructure, the upgrading of the industrial structure has been promoted, and a new growth point has been provided for the development of the national economy [ 9 ]. Other researchers believe that the establishment and use of infrastructure in a developing country have a very critical significance in promoting the long-term sustainable development of its economy and society.…”
Section: Introductionmentioning
confidence: 99%
“…Barro [45], however, noted that government investment (in this instance, infrastructure projects) will only increase the returns to firms through private investment if the positive effect of the project's investment is higher than the adverse impact of the rate of taxation required to finance the project [33,45]. This hypothesis was supported by empirical evidence from Japan, which showed that large-scale investment in public infrastructure boosted productivity when the rate of taxation used to finance it was low-but is counterproductive when financed at a high tax rate [46]. Utilizing the above theories, Crafts [33] and McMillan [47] provided explanatory equations for this theoretical premise.…”
Section: Endogenous Growth Theorymentioning
confidence: 96%
“…Specifically, empowering the European Commission Investment Plan for Europe, which is known as the EU Infrastructure Investment Plan, 23 with the aim to unlock public and private investments in the real economy. As research from Apergis and Apergis (2018) indicates, infrastructure investments 24 are endogenous to economic growth and the margin from investing in countries with already advanced infrastructure is non-existent compared to the massive return on investments from investing in countries with low infrastructure. For instance, in a country like Greece, 25 we observe that from the total of 75 infrastructure and innovation projects requested funding across all Eurozone countries, 49 of them were requested by Greece alone.…”
Section: Policy Implications For the Eurozonementioning
confidence: 99%